Microscale 3D Printing of Nanotwinned Copper. Issue 4 (7th December 2017) - Behroozfar, Ali; Daryadel, Soheil; Morsali, S. Reza; Moreno, Salvador; Baniasadi, Mahmoud; Bernal, Rodrigo A.; Minary‐Jolandan, Majid
Abstract: Nanotwinned (nt)‐metals exhibit superior mechanical and electrical properties compared to their coarse‐grained and nanograined counterparts. nt‐metals in film and bulk forms are obtained using physical and chemical processes including pulsed electrodeposition (PED), plastic deformation, recrystallization, phase transformation, and sputter deposition. However, currently, there is no process for 3D printing (additive manufacturing) of nt‐metals. Microscale 3D printing of nt‐Cu is demonstrated with high density of coherent twin boundaries using a new room temperature process based on localized PED (L‐PED). The 3D printed nt‐Cu is fully dense, with low to none impurities, and low microstructural defects, and without obvious interface between printed layers, which overall result in good mechanical and electrical properties, without any postprocessing steps. The L‐PED process enables direct 3D printing of layer‐by‐layer and complex 3D microscale nt‐Cu structures, which may find applications for fabrication of metamaterials, sensors, plasmonics, and micro/nanoelectromechanical systems. Abstract : Nanotwinned copper 3D structures are printed using room temperature localized pulsed electrodeposition process. The microscale structures have high density of aligned twinned boundaries with excellent mechanical and electrical properties.